2021
DOI: 10.1016/j.pmedr.2021.101646
|View full text |Cite
|
Sign up to set email alerts
|

Identifying factors affecting diabetes education program participation within a metro Detroit integrated health system

Abstract: Highlights Classification and regression tree analysis identified patterns in participation. White people, >43 years old, with A1c > 8.9 and with Medicaid had lowest contact. People with Medicaid, <48 years, and A1C > 8.1 had lowest intake session attendance. Older males with A1c ≤ 8.3% had the highest rate (66.0%) of completing their plan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…6 More recently, a 2020 analysis of data from a network of federally qualified health centers (FQHCs) found a low DSMES completion rate of 13% 10 ; a 2021 analysis of data from a health system found a completion rate of 13.2%. 11 Taken together, existing studies show that more than 80% of patients who start DSMES do not complete the DSMES curriculum. While the consequences of this low completion rate are unknown, the underutilization of this evidence-based, effective resource The underutilization of DSMES may be due to a lack of understanding or knowledge of the benefits, cultural factors, a desire to keep diabetes private due to perceived stigma and shame, or lack of family support.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…6 More recently, a 2020 analysis of data from a network of federally qualified health centers (FQHCs) found a low DSMES completion rate of 13% 10 ; a 2021 analysis of data from a health system found a completion rate of 13.2%. 11 Taken together, existing studies show that more than 80% of patients who start DSMES do not complete the DSMES curriculum. While the consequences of this low completion rate are unknown, the underutilization of this evidence-based, effective resource The underutilization of DSMES may be due to a lack of understanding or knowledge of the benefits, cultural factors, a desire to keep diabetes private due to perceived stigma and shame, or lack of family support.…”
Section: Discussionmentioning
confidence: 99%
“…The 2017 American Association of Diabetes Educators practice survey of diabetes educators reported that only 23% of DSMES participants completed 75% or more of the program 6. More recently, a 2020 analysis of data from a network of federally qualified health centers (FQHCs) found a low DSMES completion rate of 13%10; a 2021 analysis of data from a health system found a completion rate of 13.2% 11. Taken together, existing studies show that more than 80% of patients who start DSMES do not complete the DSMES curriculum.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They recommend that DSMES teams work to identify and respond to the social needs of people with diabetes ( Young-Hyman et al, 2016 ). Our previous analysis of demographic patterns in patient participation in diabetes management programs showed that those who did not attend their intake appointment tended to have Medicaid insurance, be aged younger than 48 years, and have hemoglobin A1c > 8.1 % ( White-Perkins et al, 2021 ). In this current study, we aimed to quantify the frequency and reported urgency of the social needs of people referred to our DSMES programs and to assess how the information reported was associated with glycemic control.…”
Section: Introductionmentioning
confidence: 99%